Urban tree planting: a strategy to mitigate global warming (2014)
The article takes a closer look at urban tree planting in relation to current global warming concerns. Trees capture and store CO2 so they directly help to avoid the earth heating up, directly. Trees also decrease temperature in open space,  minimizing urban heat islands, diminishing solar radiations impact on constructions and, therefore, reducing electricity usage for air conditioning— helping power plants drop their CO2 emissions for energy generation. Some cities are beginning to take advantage of these and other benefits of urban tree planting, but in most cases its planning follows a landscaping and aesthetic approach that largely has an effect on urban infrastructures. The article concludes that academic programs in architecture and urban planning and design should promptly include in their curriculums the study of urban tree planting from an environmental and ecological perspective so urban trees are no longer simply decorative elements, not to mention artificial decorative elements, but a strategic resource to actively mitigate global warming